Risk and protective factors of quality of life for children with autism spectrum disorder and their families during the COVID-19 lockdown. An Italian study. (January 2022) - Logrieco, Maria Grazia; Casula, Laura; Ciuffreda, Giuseppe Niccolò; Novello, Roberta Lucia; Spinelli, Maria; Lionetti, Francesca; Nicolì, Ilaria; Fasolo, Mirco; Giovanni, Valeri; Stefano, Vicari
Highlights: Quality of Life of children with Autism and their parents worsened during lockdown. Telehealth therapy is a protective factor for children quality of life. Some home activities are protective factors for children quality of life. Worsening of autism symptoms is a risk factor for parents and children quality of life. Parent reported original survey and PedsQL. Abstract: Background: The lockdown due to the COVID-19 pandemic has been a difficult period for children with Autism Spectrum Disorder (ASD), and their families. Aims: The aim of this study was to investigate the predictors of the quality of life (QoL) of children with ASD and their parents throughout the first lockdown, providing a snapshot of the impact of the pandemic on these families life. Method and procedures: A cohort of 243 parents of children with ASD (2–15 years old) completed an original online survey regarding the modification of ASD cores symptoms during lockdown, the type of interventions they had done before and during lockdown and the activities performed by the child. Respondents filled the PedsQL for themselves and their children. Outcome and results: The data obtained show a worsening of specific ASD core symptoms during lockdown and their role in predicting parents and children's QoL. Furthermore, protective factors for a better children's QoL as the Telehealth intervention, and some activities done at home during the lockdown as physical activity and play with parents are identified. Conclusions: This study identifies the QoL's risk and protective factors for children with ASD and their families. Furthermore, reveals the fundamental role of the parents as children's QoL protective factor, suggesting a higher collaboration between families and health care providers, whilst potentially improving families and children's QoL.